Review and discussion of homogenisation methods for climate data - Ribeiro, Sara (2019)
Ribeiro, S., Caineta, J., & Costa, A. C. (2016). Review and discussion of homogenisation methods for climate data. Physics and Chemistry of the Earth, 94, 167-179. https://doi.org/10.1016/j.pce.2015.08.007----- The authors gratefully acknowledge the financial support of “Fundação para a Ciência e Tecnologia” (FCT), Portugal, through the research project PTDC/GEO-MET/4026/2012 (“GSIMCLI – Geostatistical simulation with local distributions for the homogenisation and interpolation of climate data”).